Transformative learning experiences of students in repurposed service-learning projects during COVID-19 at a University of Technology - Singh, Shah Gershom (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
The potential of transformative learning through repurposed service-learning initiatives is explored by examining the transformative learning experiences of three first-year Communication students of Marketing from a university of technology in South Africa while implementing service-learning projects during the COVID-19 pandemic. To examine the differences between service-learning projects during the pandemic and the traditional face-to face models, traditional service-learning frameworks are explored and the motivation for adapting traditional service-learning is explained. The study used a qualitative research approach to examine the viewpoints of participants. To assess student transformative learning, the Transformative Learning Theory is employed as a lens. Participants were interviewed and their verbatim statements constituted the data analyzed using thematic analysis. A deductive coding approach was used as data was analyzed and a set of established themes served as the foundation for the discussion of the findings. The transformative learning experiences of the participants are discussed to illustrate how service-learning projects can be repurposed. It is evident that communication skills were practiced, and transformative learning occurred. As a result, "home-based" service-learning is recommended as a form of alternative service learning. The article contributes to the current education climate in which teaching methodologies require increased flexibility and innovation.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Communication skills; COVID-19; Experiences; Higher education; Service learning; Transformative; Transformative learning; Service learning; COVID-19 (Desease); Education, Higher